TINJAUAN FILOSOFIS TENTANG HEREDITAS, LINGKUNGAN, DAN KEBEBASAN DALAM PENDIDIKAN ISLAM - Arif Ridha (Sekolah Tinggi Ilmu Tarbiyah (STIIT) Ahlussunnah Bukittinggi, 2019)
Various educational experts, psychologists, biologists, to date still debate about the factors that most affect in human development, namely heredity and environment. Some consider heredity to be the most superior, while others argue that education in the environmental sense has a profound effect. In the end a stream appears to mediate both of these opposites, the flow of convergence. Convergence flow seeks to integrate these two factors in human development, especially in the formation of personality and potential. The basic potential is actually the nature possessed by every human being from birth, and after that the environment that fosters the potential to grow its maximum. So they can not be separated for each other to achieve maximum results.